Operational Innovation Design Using The Blue Ocean Strategy Approach To Increase Project Production Cost Efficiency At PT. Kiabadi Jaya Fasadindo - Susan Setyawan; Eric Harianto (Eduvest - Journal of Universal Studies, 2025)
Management experiences a phenomenon related to project production costs that are getting higher and often not in accordance with the Gross Profit (GP) target standards that have been set jointly at the beginning of the period. Production costs are the main factor that affects increasing the company's profitability. Management wants the company to be more efficient in project production costs, so that it is able to bring in good profits for the company's operational sustainability and growth. Therefore, management needs to evaluate various factors that affect project production costs so that efficiency can be created and reduce standard costs that determine the company's profitability. The purpose of this study is to identify the factors that make the project production cost swell, analyze the cost factors that need to be prioritized in the implementation of efficiency programs, and design action plans or improvement strategies to ensure the achievement of cost efficiency. This research was carried out through the blue ocean strategy approach method using two analysis tools, namely the strategy canvas and the ERRC grid, in designing an effective operational innovation strategy that focuses on value innovation, so as to be able to increase the efficiency of project production costs at PT. Kiabadi Jaya Fasadindo. Referring to the results of the research, the company is still able to improve the efficiency of project production costs in 2 ways, namely improving the competence of Human Resources (HR) with relevant HR development strategies that focus on increasing competence.